Educating for Vocation: Weaving Educational Ideas With Institutional Practices. Issue 1 (15th March 2017) - Roels, Shirley J.
ABSTRACT: Theologies of vocation are essential in order to explore questions of purpose, values, and direction with college and university students. Given that educational institutions have embedded values and perspectives, some higher education cultures are more effective than others in fostering a student's sense of life calling. In this article, I consider how college and university leaders consciously weave together their educational ideas about vocation with institutional practices. First, I describe diverse institutions engaged in an education for vocation. The description is based principally on learning and experience among accredited "private" colleges and universities within the United States, meaning that they are not government-sponsored institutions. Most of these not-for-profit institutions were founded by—and are still sponsored in association with—some tradition of Christian faith. Then in this article I stress that such faith-related colleges and universities must work from within the institution's mission and culture to shape the outgrowth of their vocational initiatives. Finally, I address strategies for assessment and change that match institutional aspirations with educational outcomes effectively.